Proximity to Major Roadways is a Risk Factor for Airway Hyper-Responsiveness in Adults. Issue 2 (2012) - Riley, Shannon; Wallace, Julie; Nair, Parameswaran
Abstract : BACKGROUND: Proximity to major roads is reported to be associated with asthma and airway hyper-responsiveness in children. Similar studies using objective measurements in adults are not available in Canada. OBJECTIVE: To test the hypothesis that adult asthmatic patients who live close to major roads and highways in an urban environment are at a risk of moderate to severe airway hyper-responsiveness. METHODS: Airway responsiveness was determined using methacholine bronchial provocation (PC20 ) tests in a cohort of 2625 patients who attended an outpatient clinic in Hamilton, Ontario. Patient addresses were geocoded in a geographic information system to determine proximity to major roads and highways. Multivariate linear and multinomial regression analyses were used to assess whether proximity to roads was a risk factor for airway hyper-responsiveness as measured by PC20 methacholine. RESULTS: Patients who lived within 200 m of a major road had increased odds (OR 1.38 [95% CI 1.04 to 1.85]) of having moderate airway hyper-responsiveness (0.25 mg/mL 20 <2.0 mg/mL) compared with having a normal response (PC20 >16 mg/mL). Spatial analysis also revealed that the majority of patients with severe airway hyper-responsiveness lived within the urban core of the city while those with moderate to mild hyper-responsiveness were also dispersed in rural areas. CONCLUSIONS: In an adult population of patients attending an outpatient respiratory clinic in Hamilton, living close to major roadways was associated with an increased risk of moderate airway hyper-responsiveness. This correlation suggests that exposure to traffic emissions may provoke the pathology of airway hyper-responsiveness leading to variable airflow obstruction.